1997
DOI: 10.1007/bf00387586
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of patients after hip disarticulation

Abstract: We review rehabilitation of patients after hip disarticulation operated on over the past 5 years. Sixty-two patients underwent 63 hip disarticulations: 24 had malignancies, 23 arteriosclerosis, 11 Buerger's disease, 3 diabetes and 1 uncontrollable infections. The mean age of tumour patients was 39 years (range 6-69 years), that of the vascular patients was 55 years (range 33-78 years). The postoperative mortality rate of the vascular patients was 16/37, and 0/24 of those with malignancies. There was one bilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 7 publications
0
32
0
Order By: Relevance
“…Predictably, complications after hip disarticulation are frequent, not only due to the extent of surgery, but also because patients often present extreme situations, with multiple comorbidities and hemodynamic instability. The literature presents controversial results on mortality after hip disarticulation; the rates vary according to the indication, clinical status of the patient, and the degree of urgency of the surgery 6, 7, 8, 9, 10. In the present study, it is evident that the best survival rates were observed in elective surgery, particularly in infectious and tumor causes.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Predictably, complications after hip disarticulation are frequent, not only due to the extent of surgery, but also because patients often present extreme situations, with multiple comorbidities and hemodynamic instability. The literature presents controversial results on mortality after hip disarticulation; the rates vary according to the indication, clinical status of the patient, and the degree of urgency of the surgery 6, 7, 8, 9, 10. In the present study, it is evident that the best survival rates were observed in elective surgery, particularly in infectious and tumor causes.…”
Section: Discussionmentioning
confidence: 60%
“…Presence of ischemia associated with limb infection and heart disease was the greatest predictor of mortality. Dénes and Till 7 analyzed a series of 63 dislocations, whose indications were arterial ischemia ( n  = 34), tumor ( n  = 24), and infection ( n  = 4). Surgical wound complications were observed in 64.86% of the patients whose disarticulation had vascular cause and in 20.83% of those with tumor cause.…”
Section: Discussionmentioning
confidence: 99%
“…The main reason was related to the especial design of socket of this prosthesis which encloses the pelvic [4, 7]. Therefore, the range of motion of pelvic was significantly restricted in both sides as the upper brim of the socket also surrounded the trunk.…”
Section: Discussionmentioning
confidence: 99%
“…The main reasons for amputation at this level are vascular impairment, malignancy, and tumor [1, 3]. Those with hip disarticulation miss their abilities to stand and walk efficiently (without use of crutch or walker) and have to use especial prosthesis [2, 4]. Various types of components have been designed for hip disarticulation and hip pelvectomy to enable the subject to stand and walk [4, 5]; however, they have several problems including high energy consumption during walking, slow walking speed, style of walking which is not cosmetically appealing, and limitation in range of motion of leg joints [610].…”
Section: Introductionmentioning
confidence: 99%
“…All subjects have serious diseases and undergo a deconditioning process that begins before their surgery and continues after. Young HD amputees with no serious underlying disease may recover from a deconditioned state relatively easily, giving them high probability of success in prosthetic walking [1][2][10][11].…”
Section: Introductionmentioning
confidence: 99%